Air Quality Deterioration of Urban Areas Caused by Wildfires in a Natural Reservoir Forest of Mexico - Noel Carbajal; Luis F. Pineda-Martinez; Flor Bautista Vicente (Advances in Meteorology)
Many regions of the world suffer loss of vegetation and reduced air quality due to wildfires. Studies on aerosol emissions by wildfires often discuss the negative effects of atmospheric contaminants from a regional or mesoscale perspective. The occurrence of wildfires reveals that a high percentage takes place close to large urban areas. Very high concentration of pollutants and PM10 particulate matter reach urban zones and millions of inhabitants. These events of high pollutant concentrations are seasonally recurrent. There are many large urban areas in the world that often undergo severe air deterioration due to wildfires smoke. We document the extreme impact of wildfire that occurs in the Protected Area of Flora and Fauna La Primavera located in neighborhood of Guadalajara, a large urban zone in Mexico. The simultaneous emissions of aerosols by 60 wildfires were simulated and compared with observed data. The plume generated by the wildfires reached large areas of the central part of Mexico. The principal characteristics of smog emissions (CO, NO2, and PM10) over the urban area were acceptably reproduced. Observed and modeled CO, PM10, and NO2 data indicated that aerosol plumes generated by the wildfires increased notably the concentrations over the metropolitan zone of Guadalajara.